Establishing the Feasibility of Group Metacognitive Therapy for Anxiety and Depression in Cardiac Rehabilitation: A Single-Blind Randomized Pilot Study - Wells, Adrian; Reeves, David; Heal, Calvin; Fisher, Peter; Davies, Linda; Heagerty, Anthony; Doherty, Patrick; Capobianco, Lora (Frontiers in Psychiatry, 2020)
Background: Anxiety and depression are common in cardiac rehabilitation (CR) patients. However, CR programmes which incorporate psychological techniques achieve modest reductions in emotional distress. More efficacious interventions that can be easily integrated within services are required. A promising alternative to current psychological interventions is metacognitive therapy (MCT). The aim was to evaluate the acceptability and feasibility of delivering group-MCT to CR patients experiencing symptoms of anxiety and depression. Method & Results: Fifty-two CR patients with elevated anxiety and/or depression were recruited to a single-blind randomised feasibility trial across three UK National Health Service Trusts and randomized to usual CR or usual CR plus six weekly sessions of group- MCT. Acceptability and feasibility of adding group-MCT to CR was based on recruitment rates, withdrawal and drop-out by the primary end-point of 4 months, number of MCT and CR sessions attended, completion of follow up questionnaires and ability of the outcome measures to discriminate between patients. The study was also used to re-estimate the required sample size for the full-scale trial. We also examined the extent by which non-specialists adhered to the group-MCT protocol. Group-MCT is feasible and acceptable for CR patients with anxiety and depression. Recruitment and retention of participants was high, and attendance rates at CR were similar for both groups. Conclusion: The results suggest the addition of MCT to CR did not have a negative impact on retention and support a full-scale trial of group-MCT for cardiac patients.